Variable factor shares and the index number problem: a generalization (2016)
Factor shares vary over time and across countries, so incorporating variable factor shares into growth and development accounting is both warranted and desirable. However, variable factor shares create an index number problem in analyses relying on our most commonly used production functions. We show that in the presence of competitive factor markets, the problem exists for all workhorse production functions exhibiting constant returns to scale. Therefore, any efforts to align empirical growth research with the reality of the factor share data cannot be carried out using standard techniques. New techniques need to be developed.